The Clitocybins and 2-Substituted-Isoindolin-1-Ones: Synthesis and in Vitro Antimycobacterial Activities - Mejai, Amani; Rakotoarivelo , Nambinina V.; Najahi , Ennaji; Perio , Pierre; Hollande, Etienne; Pasca, Maria Rosalia; Abidi, Rym; Nepveu , Françoise (JOURNAL OF ADVANCES IN CHEMISTRY, 2019)
Despite strong indications of antimycobacterial activities for clitocybins reported since 1945, no reports linking chemical structure and activity have been reported in the literature since then. In this study, we synthesized some clitocybin derivatives (also called 2-substituted-isoindolinones), and tested their activities and carried out some chemical derivations. Isoindolinones were prepared from methyl 2-formyl-3,5-dimethoxybenzoate and various primary aromatic amines. Compounds were evaluated for in vitro activity against Mycobacterium tuberculosis H37Rv, as well as for cytotoxicity (CC50) on the Vero cell line. 4,6-dihydroxy-2-(4-hydroxyphenyl)isoindolin-1-one, 7, and 4-hydroxy-2-(4-hydroxyphenyl)-6-methoxy-isoindol-1-one, 5, exhibited the highest antimycobacterial activities (minimum inhibitory concentration = 19.45 µM and 18.45 µM, respectively) and were non-toxic (CC50 = 30 µM and 29 µM, respectively).